Analysis of the Dynamics of the Lower Drill String Assembly in a Deep Well Coring Operation - Liu, Bin; Yao, Kunpeng; Yao, Jianlin (International Journal of Natural Resources and Environmental Studies, 2024)
In order to carry out the geological characteristics, evolution law and other scientific research of the deep strata in the extra-deep well, it is necessary to carry out the coring operation in the extra-deep depth. However, with the increase of drilling depth, the force of drill string in the underground becomes more and more complicated, and there is contact collision between the core and the core after the core tool is bent, which makes the core broken. Clarifying the dynamic behavior of the BHA during the extra-deep well coring process is helpful to obtain a more complete core. Therefore, this paper adopts the simulation analysis method to simulate the coring process of the extra-deep well with a 163.5mm diamond bit and a 140mm corer under the real drilling hole trajectory. The stress, eddy motion and the contact between the inner barrel of the core tool and the core of the lower 1000m drill assembly are analyzed. The results show that the hole expansion rate of coring bit is 2.5% in the process of low bit weight and low rotational speed. When the core is 8m, the core barrel is under compression, bending and torsion, and under the restriction of the centralizer and the core hole, the middle and upper part of the core tool bend greatly, and the contact degree with the core is high, and the larger contact force is easy to cause the lower core to fracture.